(untitled) (Ágora de Heterodoxias, 2023)
For years, small and medium-sized enterprises have made a positive contribution to the global economy, not only because they generate a large number of jobs, but also because they contribute significantly to the region’s economic development. Due to the above, an investigation was carried out in the municipality of Benito Juárez, state of Sonora, which aims to determine the relationship between the managerial skills of creative problem solving, motivation and emotional intelligence of managers of small and medium-sized companies. due to competitiveness and that allows generating a proposal for a management model that makes its processes more efficient. The type of study was correlational and descriptive with a quantitative approach that addresses a social problem from the perspective of the company’s director.106 managers of small and medium-sized companies were interviewed through the application of a questionnaire and with the support of the statistical software SPSS v.25. The results obtained accurately identify the relationship that exists between the variables involved, which allows us to conclude that there is, at least, one managerial ability directly related to the competitiveness of the company.